FROM ROOMS TO ENVIRONMENTS: TECHNO-SHORT-SIGHTEDNESS AND LANGUAGE LABORATORIES - Perez Paredes, Pascual (International Journal of English Studies, 2002)
Language laboratories have played a major role in the history of foreign language teaching. However, when regarding their presence in modern post-20th century foreign language teaching and learning, it is difficult to find in the profession a close adherence to the concept of language laboratory( Howatt 1984). As a succinct explanation, it has been argued that with the rise of Communicative-based Language Teaching they were neglected and became a useless technology. ln this position paper we will discuss the role of language laboratories in retrospective. paying attention to the technology diffusion process which accounted for their initial success, and contributing arguments for a revision of their historical evolution into a new tool for learning and teaching foreign languages. Tlie notion of techno-short-rightednrss will be used to describe the process of diffusion and media adaptation of the language laboratory technology to the latest language learning paradigins. The article includes a survey of existing language laboratory technologies as well as a tasonomy based on their functions and information delivery systems.